(untitled) - Bailey, Brian J.; (1925-2012) (Philippines, 1997)
Soldiers For Christ is an exciting, easy to understand, verse by verse exposition on Paul's letter to the Ephesians. The Epistle to the Ephesians portrays Christ as the warrior King, clothed with the armor of God. This same armor is available to us by His grace so that we too may be victorious over the enemy. Soldiers For Christ explains what it means to put on the armor of God.
Keywords: Bible -- Ephesians -- Commentaries